2000
DOI: 10.1128/jvi.74.18.8524-8531.2000
|View full text |Cite
|
Sign up to set email alerts
|

Retracing the Evolutionary Pathways of Human Immunodeficiency Virus Type 1 Resistance to Protease Inhibitors: Virus Fitness in the Absence and in the Presence of Drug

Abstract: Human immunodeficiency virus type 1 (HIV-1) resistance to protease inhibitors (PI) is a major obstacle to the full success of combined antiretroviral therapy. High-level resistance to these compounds is the consequence of stepwise accumulation of amino acid substitutions in the HIV-1 protease (PR), following pathways that usually differ from one inhibitor to another. The selective advantage conferred by resistance mutations may depend upon several parameters: the impact of the mutation on virus infectivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
153
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(167 citation statements)
references
References 50 publications
14
153
0
Order By: Relevance
“…Single mutations in protease produced varied effects on replication capacity. The L90M, I47V, and M46I mutants exhibited higher replication capacity than WT, consistent with a previous study (46). The protease mutants I50V and I47A had highly impaired replication capacity (<0.1) relative to WT.…”
Section: Effect Of Resistance Mutations On Replication Capacity and Ssupporting
confidence: 78%
See 1 more Smart Citation
“…Single mutations in protease produced varied effects on replication capacity. The L90M, I47V, and M46I mutants exhibited higher replication capacity than WT, consistent with a previous study (46). The protease mutants I50V and I47A had highly impaired replication capacity (<0.1) relative to WT.…”
Section: Effect Of Resistance Mutations On Replication Capacity and Ssupporting
confidence: 78%
“…Therefore, determining inhibition at clinical concentrations requires a method for extrapolating from IC 50 to higher concentrations. IC 90 is sometimes used (46,49); however, like IC 50 , it represents only a single point on the dose-response curve. However, m describes how inhibition changes with drug concentration, and is thus critical for understanding drug effects at clinical concentrations.…”
Section: Analysis Of Resistance Mutations Using Primary Cells Vs Tramentioning
confidence: 99%
“…A number of studies have demonstrated that a K103N mutation has little effect on viral fitness, 7,8 whereas protease inhibitor signature mutations exact a fitness cost. 9,10 Our results would arise from addition of the new mutations at failure of the second regiment to the most fit virus. Numerous in vitro studies have looked at the fitness of an HIV virus with mutations that occur after the failure for the therapies shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…V82T, which is one of the substitutions at codon 82 that confer broad crossresistance, was also significantly reduced in fitness compared to that of the wild-type virus (118). V82A, which confers low-level but broad cross-resistance, did not demonstrate significantly reduced fitness in a single-cycle assay but did have a replicative advantage compared to wild-type virus in the presence of drug (109). Consistent with these results from site-directed mutants are studies of serial clinical isolates obtained from patients failing protease inhibitor therapy that have correlated the development of reduced fitness in the Monogram RC assay with the emergence of V82A, I84V, or L90M (14).…”
Section: Mutations Conferring Resistance To Protease Inhibitorsmentioning
confidence: 99%
“…G48V, which is a major mutation conferring resistance to saquinavir, was shown to have decreased fitness in a singlecycle assay (109). I50L, which confers resistance to atazanavir, also has reduced fitness in parallel infections (34).…”
Section: Mutations Conferring Resistance To Protease Inhibitorsmentioning
confidence: 99%